Supporting respiratory patients in primary care: a qualitative insight from independent community pharmacists in London - Iman Hesso; Reem Kayyali; Shereen Nabhani-Gebara (BMC, 2019)
Abstract Background Community pharmacists' (CPs') interventions have a positive impact on managing respiratory patients. However, methods used by CPs to assess patients' inhaler technique and adherence are subjective. New technologies to objectively assess inhaler technique and adherence were introduced to address such a gap. This study aimed to explore CPs' perceptions towards the management of respiratory patients regarding inhaler technique and adherence. In addition, it explored the views of CPs and their need of technologies to objectively assess inhaler technique and adherence. CPs were probed with a new technology called Inhaler Compliance Assessment (INCA) device, designed to objectively monitor both inhaler technique and adherence of patients using a dry powder inhaler, as an example. Methods A qualitative study employing semi-structured interviews was conducted. A convenience and snowballing sampling strategy was employed to recruit CPs working in independent community pharmacies within West and South London. Twenty-three pharmacists were interviewed between August and November 2015. Data was analysed thematically using the framework methodology and coded using NVivo10 software. Results Analysis revealed five main themes: services and limitations of patient support, the need and acceptability of new technologies to support respiratory patients, fragmented primary care, the need to promote the clinical role of CPs, and professional identity. Patient support was patchy and affected by several barriers related to pharmacists and patients. In addition, lack of communications with different healthcare professionals in primary care and inaccessibility to clinical records were identified as problematic issues. Some CPs perceived their clinical role to be lacking within the patient care pathway. Interestingly, CPs showed positive a attitude towards the use of technologies, such as the INCA technology to support patients and were willing to provide new services. However, remuneration appeared to be a major driver for willingness to offer new services or promote existing services. Conclusion The current study highlighted some measures that can augment CPs' clinical practice while managing patients, such as having accessibility to patients' medical records and the use of technologies such as the INCA technology to promote objective counselling of patients.